From poverty to well-being: The potential and strategy of the Kelantan islamic religious and Malay customs council (MAIK) in empowering productive asnaf in Kelantan - Nooramira Ghazali; Nadiah Rus Liyana Rusli; Wan Nur Izzati Wan Nor Anas; Hawa Husna Ab Ghani; Kauthar Razali (Human Resource Management Academic Research Society (HRMARS), 2024)
Poverty is a multifaceted issue that profoundly impacts economic stability, health, and educational opportunities. This is especially evident in Malaysia’s states of Sabah, Sarawak, Kelantan, and Kedah. Despite concerted governmental efforts to eliminate extreme poverty in these regions, significant challenges remain. In Kelantan, the Kelantan Islamic Religious and Malay Customs Council (MAIK) has taken a substantial role in poverty alleviation, with a specific focus on supporting aṣnāf groups. This study addresses the question: What potential strategies should MAIK implement to guarantee sustainable progress in reducing poverty? It seeks to assess both potential strategies and the operational mechanisms of poverty alleviation within MAIK. This study uses a qualitative case study approach, collecting data through unstructured interviews with MAIK representatives and supplementing it with secondary sources, including academic literature and official publications. Thematic content analysis of this data reveals four critical areas of potential, including the strategic selection of productive aṣnāf and effective knowledge transfer practices.